Peace In Islam In The Light Of The Holy Quran And Hadith - Nasir Hassan Wani (LECTURES: Journal of Islamic and Education Studies, 2023)
Islam is a peaceful, merciful, tolerant, and most kind religion. It is a divine religion. To advance and defend justice and peace, it confronts every cruelty, violence, and viciousness. The goal of the entire Islamic ethical system is to uphold society's overall state of peace, safety, and happiness. This code emphasizes unity and all righteous actions that promote peace and forbids any action that promote violence. Therefore, if the society's members follow Islamic ethics, they will surely experience peace, safety, and satisfaction. All Islamic moral principles result in a better individual who is an upright human being who possesses the admirable qualities of honesty, justice, courage, generosity, patience, and kindness. For Muslims and non-Muslims alike, justice and peace are necessary and important in all circumstances, whether one is joyful and satisfied or disturbed and dissatisfied. This paper focuses on how the holy Qur’an and the traditions of Prophet of Islam (PBUH) teach its followers to obey and uphold the divine laws so that everyone in the society feels safe and comfortable and also educate them to be kind and to like for others as wishes for themselves so that everyone in the society benefits. This paper concludes with the argument that Islam seeks to construct the ideal human society and brotherhood, spreading all-around goodness and divine direction among people for their benefit and betterment.